2020
DOI: 10.1016/j.ijfoodmicro.2019.108498
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of non-ochratoxigenic Aspergillus carbonarius strains and interactions between some black aspergilli species

Abstract: Aspergillus carbonarius consistently produces large amounts of ochratoxin A (OTA), a mycotoxin with nephrotoxic effects on animals and humans. In the present study, we analyzed the transcriptional changes associated to OTA production in three atypical non-ochratoxigenic strains of A. carbonarius. In addition, in vitro interactions between ochratoxigenic strains of A. carbonarius and A. niger and non-ochratoxigenic strains of A. carbonarius and A. tubingensis were studied in order to evaluate their potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…For the genes otaE and otaR2 located close to the OTA-putative gene cluster, the expression pattern under different carbon sources was different. This result could be an evidence for the unnecessary role of the two genes in OTA biosynthesis, confirming the results obtained for A. carbonarius, another main OTA-producing fungus and other OTA-producing fungi [11,12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For the genes otaE and otaR2 located close to the OTA-putative gene cluster, the expression pattern under different carbon sources was different. This result could be an evidence for the unnecessary role of the two genes in OTA biosynthesis, confirming the results obtained for A. carbonarius, another main OTA-producing fungus and other OTA-producing fungi [11,12].…”
Section: Discussionsupporting
confidence: 89%
“…In 1993, OTA was listed as a possible carcinogenic substance (group 2B) by the International Agency for Research on Cancer [7]. Based on a comprehensive understanding of the dangers of OTA, researchers have paid more attention to the biosynthetic and regulatory mechanism of the toxin in the producer species [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Other general regulatory genes, such as veA and laeA, impact mycotoxin production [16,21]. Previous research has demonstrated that co-inoculation of an OTA-producing A. carbonarius strain with a non-OTA-producing A. carbonarius strain, which harbors a Y728H mutation in the otaA gene, can lower OTA levels [29]. If, as suggested by the authors, failed OTA production in this strain is due to a single point mutation, then there is a chance that this mutation can be reversed and lead back to an OTA-producer strain.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq analysis showed 280 upregulated genes and 333 downregulated genes. Functional and GO enrichment analyses showed the downregulation of processes related to metabolic and oxidative processes as well as functions related to oxidoreductase and hydrolase activities [52].…”
Section: Discussionmentioning
confidence: 99%